2003
DOI: 10.1039/b305633c
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneously catalysed selective hydrogenation reactions in ionic liquids

Abstract: The selective hydrogenation of a,b unsaturated aldehydes has been performed in a range of room temperature ionic liquids. The reaction data reported show that it is possible to enhance the selectivity of supported palladium catalysts for the reduction of the conjugated CNC bond by using ionic liquids as solvents compared with conventional molecular organic solvents. The catalyst system is easily recycled without the need to isolate or filter the catalyst and may be used without further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 45 publications
2
66
0
2
Order By: Relevance
“…For applications of ILs in the field of catalysis, two directions recently discussed in the literature are particularly attractive: -ILs are not only interesting solvents for homogeneous catalysis but also for heterogeneously catalyzed reactions [19][20][21]. For example, Xu et al [21] showed that ILs are excellent media for the hydrogenation of halonitrobenzenes to the corresponding haloanilines over Raney nickel, carbon-supported platinum and palladium.…”
Section: Introductionmentioning
confidence: 99%
“…For applications of ILs in the field of catalysis, two directions recently discussed in the literature are particularly attractive: -ILs are not only interesting solvents for homogeneous catalysis but also for heterogeneously catalyzed reactions [19][20][21]. For example, Xu et al [21] showed that ILs are excellent media for the hydrogenation of halonitrobenzenes to the corresponding haloanilines over Raney nickel, carbon-supported platinum and palladium.…”
Section: Introductionmentioning
confidence: 99%
“…The product was then dried under high vacuum for 4 h to give viscous liquid at 20 • C in 91% yield (3.87 g, 9.97 mmol). 1 …”
Section: Preparation Of 3-methyl-1-(2-(2-methoxyethoxy)-ethoxycarbonymentioning
confidence: 99%
“…The product remaining was dried on the rotary evaporator and then under high vacuum for 8 h to yield a yellow grease in 85% yield (3.33 g, 7.62 mmol). 1 …”
Section: Preparation Of 3-methyl-1-(2-(n-propoxy)ethoxycarbonylmethylmentioning
confidence: 99%
“…The reaction rates were found to be lower in [bmim] [BF 4 ] than in methanol, which was attributed to mass transfer processes. Anderson et al [43] selected the , -unsaturated aldehydes, citral and cinnamaldehyde ( Figure 9 and Figure 10), to demonstrate the superior selectivity obtained using pyridinium, imidazolium and ammonium ILs over common organic solvents in hydrogenation reactions. A palladium on carbon catalyst (3) was used for the reactions.…”
Section: Transition Metal Catalysis In Ilsmentioning
confidence: 99%